The applicability of context-based multicast: a shopping centre scenario - Wozniak, Thomas (2010)
This paper analyzes the applicability of context-based multicast content distribution (CBMCD) on the example of realistic push- and videobased mobile advertising services at a shopping centre. The technical results of the simulation of the service scenario show that CBMCD significantly reduces the number of unicast streams and the total volume of traffic in the network. The results of the financial analysis show that these technical benefits can be translated into considerable financial benefits due to costs savings. Taken together, these results suggest that CBMCD can be an efficient, cost-saving network traffic management approach and the basis for lucrative push services.